Seroprevalence of Brucella abortus and B. canis in household dogs in southwestern (2011)
A preliminary serological study of 366 household dogs in Lagos and Ibadan, southwestern Nigeria, was carried out to determine antibodies due to exposure to Brucella abortus and B. canis, using the rose bengal test (RBT) and the rapid slide agglutination (RSA) test, respectively. Results showed that 5.46 % (20/366) and 0.27 % (1/366) of the dogs screened were seropositive to B. abortus and B. canis, respectively.Of all dogs, 36 had a history of being fed foetuses from cows and 11 (30.6 %) of these tested positive in the RBT. Our findings, although based on a limited sample size and a dearth of clinical details, revealed that dogs in Nigeria may be infected with Brucella spp. given the wide range of risk factors. Further studies are recommended to elucidate the epidemiology of brucellosis in dogs and its possible zoonotic consequences in the country.